Zaangażowany społecznie biznes w świetle badań w wybranych krajach Unii Europejskiej - Zbiegień-Maciąg, Lidia (Social corporate responsibility in the framework of research in the selected EU countries, 2006)
Interpersonal relations governance based on the underlying principles of Corporate Social Responsibility is becoming the core foundation of corporate competitiveness. Corporate Social Responsibility of a company has recently become a focus of the investors' attention. They not only consider the operating performance and profitability of a company, but also reflect on its social responsibility and stakeholders relations. The concept of social responsibility has been originated in the EU countries at the beginning of the nineties and it is becoming increasingly popular nowadays. The article presents selected findings based on the research at Polish, Hungarian and Slovakian companies regarding corporate social responsibility practices and management behaviour. The results show that employee relations tend to be neglected and, as a consequence, the general, social goals and objectives often become less visible.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 438-445